1310. Improving Infectious Disease Electronic Medical Records Documentation: A Quality Improvement Study in an Academic Teaching Hospital. (26th November 2018) - Lakshmi, Seetha; Asquith, Johonna; Alrabaa, Sally; Sampson, Mindy; Kraitman, Natan; Akoghlanian, Garabet; Balakrishnan, Maya; Casanas, Beata
Abstract: Background: Improving efficiency of documentation and sign outs during transitions of care were identified as areas of interest by the University of South Florida Infectious Disease (ID) Division. Our aim is by May 2018, we will achieve >50% improvement in our ID EMR note efficiency score for any adult patient at Tampa General Hospital. Note efficiency score involves listing all of the following key elements with 1 point awarded for each: active problem in the subjective section, updated hospital course under assessment, active problem prioritized first under assessment and non-relevant problems removed from assessment. Methods: Institute of Healthcare Improvement's model with Plan-Do-Study-Act (PDSA) cycles was used for project implementation from March 2018 to May 2018 (Figure 1). Cycle 1: Conducting a needs assessment survey and education. Cycle 2: Changing the existing template and implementing a new standardized template that includes the key elements, along with removal of auto populated non relevant information. Audits of notes with a 4-point system scoring was done. A pre and post implementation physician survey was conducted. Results: ID fellow and faculty completed the baseline survey ( N = 25). Less than half (46%) felt that they could interpret patient assessments with ease and even fewer respondents (36%) felt there was adequate weekend sign out. More than one-third (36%) reported writing majority of notes after 5 pm (Figure 1). Pilot project involved nine ID faculty and fellows. We had 95% compliance with use of the standardized EMR template. Notes were evaluated at baseline ( n = 190), cycle 1 ( n = 85), and cycle 2 ( n = 56). An increase in average note efficiency score from baseline, cycle 1 and cycle 2 occurred as follows (Mean ± SD): 2.0 ± 0.84 vs. 2.8 ± 0.95 vs. 3.6 ± 0.5 (Figure 2). Compared with baseline, cycle 2 achieved 42% improvement in the ease of interpretation of patient assessments and 41% improvement in adequate sign out. No increase in note writing after 5pm (36% vs. 30% baseline and cycle 2, respectively) reported. Conclusion: Targeted education and changing the EMR note template can achieve improved efficiency of ID note. These efforts to improve documentation enhance physician's ease of interpretation of patient assessments and sign out during transition of care. Disclosures: All authors: No reported disclosures.